Prevalence of criminal convictions in Norwegian adult ADHD outpatients and associations with ADHD symptom severity and emotional dysregulation - Anker, Espen (BMC Psychiatry, 2021)
OBJECTIVES: Attention deficit hyperactivity disorder (ADHD) often co-occurs with antisocial behaviour. Several studies have shown high rates of ADHD among prisoners. However, the prevalence of crime among individuals with ADHD is less known. The aim of the present study was to estimate the prevalence of lifetime criminal conviction (CC) in a clinical sample of adults with ADHD, and the associations with the severity of ADHD and emotional dysregulation (ED). METHODS: Patients were admitted to a private psychiatric outpatient clinic in Oslo between 2014 and 2018. Of the 656 patients diagnosed with ADHD, 629 (95.9%) agreed to participate in the study. CC was determined based on self-reporting of the lifetime history of criminal behaviour. ADHD was diagnosed according to the DSM-5 criteria, and ADHD severity was measured using the Adult ADHD Self-Report Scale (ASRS). ED was assessed by the eight-item version of Barkley’s Current Behaviour Scale - Self-Report (CBS-SR). RESULTS: The prevalence of self-reported CC in this clinical sample was 11.7% among women and 24.5% among men. CC was associated with hyperactive-impulsive severity (p < 0.001) and ED (p = 0.006). CONCLUSIONS: The prevalence of self-reported lifetime criminal conviction was high for both genders. CC was associated with symptom severity of hyperactivity-impulsivity and emotional dysregulation. The findings suggest the need for greater research efforts on the avoidance of criminal activity in people with ADHD and targeted intervention for ADHD treatment and CC prevention.